Desing and Mainstreaming of the student Generic Profile (Revista Electrónica Calidad en la Educación Superior, 2018)
There are growing demands of society on the need to rethink vocational training implies to look back to a training in generic skills. The object of this article is to discuss on those aspects and elements that must be considered to design a generic profile as part of the professional profile of the graduate student; that also includes the right methodological-evaluative planning for the mainstreaming of the generic skills that make up each competence. It is concluded the study plans that incorporate the generic profile in their training proposals. It is evidenced an advance towards the fulfillment of the quality standards that are being handled at an international and national level. It is also required by the accrediting agencies and in addition, students who graduate from these careers will possess skills that will make them highly competent and competitive because, in a society where demands are constantly reinventing, generic competencies are highly valued.